Adrenal neoplasms - Onur, Mehmet Ruhi; Turgut, Ahmet T.; Dogra, Vikram S.; MacLennan, Gregory T. (Springer-Verlag London Ltd, 2013)
Adrenal masses occur in 3 % of patients above 50 years of age. Adrenal adenoma is the commonest adrenal mass. Benign adrenal neoplasms include adrenal adenoma, adrenal myelolipoma, ganglioneuroma, ganglioneuroblastoma, neuroblastoma, schwannoma, paraganglioma, and hemangioma. Malignant adrenal neoplasms include adrenal metastasis, adrenocortical carcinoma, and adrenal lymphoma. Management of adrenal lesions mainly depends on the imaging findings of these masses. CT and MRI constitute most important imaging techniques in initial evaluation and follow-up of patients with adrenal masses. © Springer-Verlag London 2013.